Вокально-хорове інтонування поезії Лесі Українки у творах Михайла Довганича - Прокопович, Тетяна; Prokopovych, Tetiana (Східноєвропейський національний університет імені Лесі Українки, 2016)
У статті проаналізовано хорові твори Михайла Довганича на вірші Лесі Українки. Основну увагу зосереджено на виявленні співвідношення вербаль- ного тексту з виразовими засобами вокального багатоголосся. Композиторське інтонування Лесиного слова в хоровому звучанні переконливо підсилює мно- жинність смислів і образів високої поезії. In the article choral works of Mykhailo Dovhanych are analysed on the verse of Lesia Ukrainka. The special attention is concentrated on principles of co-operation of poetic word and music. Understanding conception and structural conformities to law of Lesia’s Ukrainka lyrics a modern composer finds out deep musicality of verbal text, Voice vividness, melodiousness of poetic intonation, dramaturgic principles of poetic form, emotional tone of verse flexibly correlates with the complex of musical expression. For own interpretation of Lesia’s word М. Dovhanych attracts the genre-stylistic resource of vocal polyphony. It gives to composer’s conception foremost nationally-mental characteristicness increase authorial melodious material within the limits of tune- intonation dictionary of Ukrainian music. The through type of development of choral miniature with changeableness of rate, dynamics, and metro-rhythm convincingly recreates emotional amplitude of literary source. Advantage of compositions for women’s (child’s) choir of a capella exposes refinement and spirituality of poetic characters of Lesia Ukrainka.
Vocal and Choral Intonation of Lesia Ukrainka’s Poetry in the Works of Mykhailo Dovhanych
Keywords: поетична музикальність; вокально-хорові твори; a capella; інтонування; силабічний принцип; poetic musicality; vocally-choral works; a capella; intoning; through development; syllabic principle